Solar efficiency of a new photo-catalyst TiO2 deposited on a photo-inert paper for the total degradation of various pesticides and dyes - Hoai Bui, Thu (2010)
A specially designed titania photocatalyst was prepared by coating Ahlstrom non-woven paper, used as a flexible photocatalytic support, with Millennium PC500 anatase. At the same time, a new solar photoreactor (STEP) was designed based on the multi-step cascade falling-film principle to ensure good exposure to sunlight and good oxygenation of the effluent to be treated. Several types of reactants were treated: 4-chlorophenol as a model organic pollutant; formetanate, a widely used pesticide in horticulture; a mixture of pesticides used in vineyards; and Indigo Carmine and Congo Red, which are complex multifunctional dye molecules. Each reaction was performed simultaneously in a solar CPC slurry photoreactor and in the STEP photoreactor under identical solar exposure to better evaluate and validate the results obtained. The STEP solar reactor was found to be as efficient as the CPC one for 4-chlorophenol and formetanate total degradation.